Desain Pembelajaran Bahasa Inggris Untuk Pendidikan Anak Usia Dini - Sophya, Ida Vera (PIAUD Universitas Islam Negeri Sunan Kudus, 2014)
Early Childhood Education is one form of the provision of educationthat focuses on the foundation of the direction of growth and development. Atan early age, children can be taught basics English only and they are taught itby directed playing. Through directed playing, children can learn many things.Instructional design is an integral part of several components of interactinglearning, interrelation and interdependence in achieving the learningobjectives that have been set. Learning component includes students, teachers,curriculum, teaching materials, instructional media, learning resources,learning processes, facilities, environment and learning objectives. Thesecomponents should be designed in accordance with the developing learningprogram.